2014
DOI: 10.1387/ijdb.140324tl
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of maternal egg size effects in sister salamander species

Abstract: Egg size varies genetically and with the maternal environment. It is correlated with and can act as a resource fueling variation in many other key life history traits. This study examined hypotheses about how plastic responses of offspring to yolk variation evolve (and contribute to phenotypic evolution) when maternal investment in egg size evolves. I used a split-clutch, controlled, surgical experiment with a longitudinal (repeated-measures) design to examine the effects of yolk removal on sister salamander s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Research in other organisms has also indicated a broad importance of variation in yolk stores to suites of offspring traits (e.g., Lancaster et al 2010, Landberg 2014, 2015), and the findings of our study add to the body of work suggesting an integrative role of yolk stores to offspring traits. Additionally, there was a weak tendency for the Surgical Control individuals to express trait values that were intermediate to the Reduced and Unmanipulated individuals (e.g., Fig.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Research in other organisms has also indicated a broad importance of variation in yolk stores to suites of offspring traits (e.g., Lancaster et al 2010, Landberg 2014, 2015), and the findings of our study add to the body of work suggesting an integrative role of yolk stores to offspring traits. Additionally, there was a weak tendency for the Surgical Control individuals to express trait values that were intermediate to the Reduced and Unmanipulated individuals (e.g., Fig.…”
Section: Discussionsupporting
confidence: 73%
“…1b). Use of this yolk manipulation technique in other Ambystoma has also indicated an effect of the Surgical Control on offspring traits (Landberg 2014, 2015), and may reflect the well‐documented response of amphibians to pre‐hatching environmental effects (e.g., Touchon et al 2013) or an artifact of our sampling design. Despite these small effects, our experimental study strongly implicates an integrative relationship between yolk stores and a suite of offspring traits.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Minimizing environmental maternal effects precludes the ability to identify the role they might play in adaptive evolution. Of course, they may play no role and represent merely an extra source of environmental variation that must be minimized before genetic distinctions can be quantified precisely (Landberg, ; Michimae, Nishimura, Tamori, & Wakahara, ; Monaghan, ). On the other hand, they might contribute substantially to forming a locally adapted phenotype.…”
Section: Introductionmentioning
confidence: 99%